A randomised trial of 5% minoxidil versus combination of 5% minoxidil and oral spironolactone in treatment of female pattern hair loss - Palaskar, Nachiket Madhukarrao; Chaudhari, Nitin Dinkar; Balpande, Garima Laxminarayan; Khatu, Swapna Subhash (International Journal of Research in Dermatology, 2019)
Background: Female pattern hair loss (FPHL) is a common form of nonscarring hair loss. We compared the usefulness and safety of topical minoxidil alone with combination of oral spironolactone and topical minoxidil in the treatment of FPHL. Methods: This prospective, single-centre, randomised open label study over 100 patients attending tertiary care hospital in Mumbai during period December 2011 to June 2012. The data were entered into SPSS version 21 for analysis. Data collected were coded and described as frequency and percentage for qualitative data and means and standard deviation for quantitative data. Statistical analysis was done using chi-square and student t test. Statistical significance was considered if p value was less than 0.05. Results: There were 48 patients in Group I and 46 patients in Group II. At 6 months, significantly higher mean Sinclair grade was observed among Group I patients as compared to Group II patients (2.85±0.68 vs 2.56±0.50, p=0.02). We observed a significant improvement in women’s androgenetic alopecia quality of life questionnaire in Group I patients at 12 months after treatment (26.93±2.25 vs 23.47±2.95, p<0.001). Minoxidil and spironolactone were tolerated well by the patients. Conclusions: Combination therapy of topical minoxidil and oral spironolactone has an additive effect. However, plateau of effectiveness of the combination therapy in normoandrogenic patients at 6 months of therapy was observed. We recommend the combination for 6 months and continuation of therapy with minoxidil only.